Scholarly adventures in digital humanities : making the modernist archives publishing project - Wilson, Nicola ; Southworth, Helen ; Staveley, Alice ; Widner, Michael ; Gordon, Elizabeth (Palgrave Macmillan, 2020)
Introduction -- 1. What is MAPP? -- 2. Who We Are -- 3. Reflections on Collaboration -- 4. Building a Critical Digital Archive -- 5. Digital Humanities in the Classroom -- 6. Public Scholarship -- Coda -- Appendix A -- Appendix B -- Bibliography -- Index.